2014
DOI: 10.1002/jssc.201400884
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of sarpogrelate and its active metabolite in human plasma by liquid chromatography with tandem mass spectrometry and its application to a pharmacokinetic study

Abstract: We established a rapid and simple liquid chromatography with tandem mass spectrometry method for the simultaneous determination of sarpogrelate and its active metabolite, M-1, in human plasma. Sarpogrelate, M-1, and the internal standard, ketanserin, were extracted from a 50 μL aliquot of human plasma by protein precipitation using acetonitrile. Chromatographic separation was performed on a Shim-pack GIS ODS C18 column (100 × 3.0 mm; 3 μm) with an isocratic mobile phase consisting of 10 mM ammonium acetate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In this study, 48 incurred samples were reanalyzed in a separate batch run. The difference was calculated with the following equation: [(reanalyzed value–initial value)/average of the two] × 100%] . The results showed that 89.6, 93.8, and 87.5% of ISR samples met the accepted criteria (within 20%) for β‐sitosterol, campesterol, and stigmasterol, respectively, indicating good reproducibility of the present method.…”
Section: Resultsmentioning
confidence: 83%
“…In this study, 48 incurred samples were reanalyzed in a separate batch run. The difference was calculated with the following equation: [(reanalyzed value–initial value)/average of the two] × 100%] . The results showed that 89.6, 93.8, and 87.5% of ISR samples met the accepted criteria (within 20%) for β‐sitosterol, campesterol, and stigmasterol, respectively, indicating good reproducibility of the present method.…”
Section: Resultsmentioning
confidence: 83%
“…The LC-MS/MS conditions for the determination of sarpogrelate and M-1 were the same as previously described. 20 The metabolic stability expressed as a percentage of the test compound (sarpogrelate or M-1) remaining was calculated by comparing the peak area ratios of sarpogrelate and M-1 to the internal standard at specific time points relative to time 0 minutes. The t 1/2 was estimated from the slope of the initial linear range of the logarithmic curve of the residual sarpogrelate (%) versus time, assuming a first-order kinetics.…”
Section: Methodsmentioning
confidence: 99%
“…The plasma concentration-time profiles of sarpogrelate and M-1 after a 100-mg oral dose of sarpogrelate obtained from a previously published study were used to build the PBPK model. 20 The PBPK model was evaluated by comparing the predicted pharmacokinetics profiles of sarpogrelate and M-1 with the observed published data. 20 24 , 41 43 Then, the predicted pharmacokinetic parameters such as AUC, C max , and time to achieve C max ( T max ) were calculated to compare with reported clinical data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study of the oral administration of sarpogrelate (100 mg) under fasting conditions, the maximum drug concentration (C max ) reached approximately 650 ng/mL at 0.67 hour, and the area under the curve (AUC) was about 690 h·ng/mL . In humans, it has been shown that sarpogrelate is quickly hydrolyzed to M‐1 and eliminated from plasma (half‐life of drug excretion in the terminal phase [t 1/2 ] ≈ 0.7 hour), which is faster than the duration of its pharmacological effects.…”
mentioning
confidence: 99%